Pengaruh Bimbingan Kelompok Melalui Zoom Meeting dengan Teknik Johari Window dalam Meningkatkan Penerimaan Diri Siswa - Afny Rumaysya Khulwah; Heru Mugiarso (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2021)
The purpose of this study was to determine the effect of group guidance services through zoom meetings with the Johari Window technique to increase student self-acceptance. Current research used experimental method with one group pre-test post-test design. The sampling technique used was purposive sampling with total of 8 sample. The data collection method is self-acceptance scale with 4 indicators and 52 items. The validity of the instrument verified using the product moment formula obtained r table value = 0.312. While the reliability of the instrument verified with the Cronbach alpha formula, the results of the Cronbach Alpha were 0.774. The data analysis technique used is descriptive analysis and Wilcoxon test. The results of the descriptive analysis showed that the level of student self-acceptance before being given treatment was in the medium category. Meanwhile, before being given treatment, they were in the high category. Based on the results of the Wilcoxon test, it is known that Asymp. Signature. (2-tailed) worth 0.012. Because 0.012 is smaller than 0.05, it can be said that group guidance services through meetings with the johari technique have a significant effect on increasing student self-acceptance.